Strategi Pengembangan Produk Tempe Berbasis Lokal pada UMKM di Desa Tanjung Tani Kecamatan Prambon Kabupaten Kediri - Mohammad Febrianto; Bambang Suwarsono; Brahma Wahyu K (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to analyze the development strategy of local-based tempeh products in MSMEs in Tanjung Tani Village, Prambon District, Nganjuk Regency. The focus of the research includes analyzing the internal and external conditions of the business and formulating strategies through the SWOT approach. The results showed that tempeh MSMEs have strengths in product quality and competitive prices, but face weaknesses in bookkeeping, digital marketing, and limited capital. Based on the Grand Strategy Matrix, MSMEs are in quadrant II, which indicates that development strategies need to be directed towards internal efficiency and adaptation to external challenges. Recommended strategies include utilizing local soybeans, improving HR skills, business legality, and product and packaging innovation. The analysis technique used in this research is descriptive qualitative analysis with the support of SWOT method, IFAS (Internal Factor Analysis Summary), EFAS (External Factor Analysis Summary), and Grand Strategy Matrix. Data were obtained through field observations, direct interviews with business actors, and distributing questionnaires to selected respondents. The IFAS and EFAS matrices were used to identify strengths, weaknesses, opportunities, and threats, which were then mapped in the Grand Strategy Matrix to determine the most appropriate development strategy direction for tempeh MSMEs in the study area.